Peran UNAIDS Dalam Menangani Masalah HIV/AIDS Terhadap Perempuan di Afrika Selatan Pada Tahun 2011-2015 - Apsari, Ni Made Listu Ayu Belia; Priadarsini, Ni Wayan Rainy; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT   This research is conducted with qualitative research method to compile how UNAIDS as an international organization tackling the problem of HIV/AIDS that effect women in South Africa. South Africa has the most people with HIV/AIDS in the world. The number of women who suffers from HIV/AIDS is higher compared to the number of male who is infected with HIV/AIDS. Women also suffers from the great impact of HIV/AIDS. UNAIDS as an international organization which works on HIV/AIDS field also highlighted the problem of HIV/AIDS against women. UNAIDS in its role as an actor has recommended a lot of policies to South Africa, which South Africa put the policies into action. Those policies has successfully make the HIV/AIDS prevalence number on women decreased.                                                 Keywords: UNAIDS, International Organization, HIV/AIDS